Handbook of soil science - Bechdal, Brian (Callisto Reference, 2015)
This book on soil science is a compilation of chapters written by international authors. These scientists have explored various aspects of soil sciences and presented them in this valuable guide for researchers in this field. This book contains case studies reflecting on all the concepts related to soil from all over the globe. It elucidates the effects of chemical, industrial and human activities on the quality of soil. We hope that this book proves to be a resourceful guide for both basic and advanced concepts in soil science.